The Relationship Between Quality of Life and Psychological Well-Being Among Breast Cancer Patients at RSUD K.R.M.T Wongsonegoro Semarang - Pricillia Veronica; Mariyati Mariyati (International Journal Of Health Science, 2026)
Breast cancer is the growth of new tissue as a result of the proliferation (excessive growth) of abnormal cells that can attack and damage other tissues causing the growth of new tissue. Breast cancer is also included in the deadly diseases and suffered by most women. Breast cancer treatment has negative side effects in the form of physical impacts such as nausea, vomiting, fatigue, and psychological impacts such as anxiety, stress, and depression. This study is to determine the relationship between quality of life and psychological well-being in breast cancer patients. This study uses a quantitative method with 47 respondents and the criteria are able to communicate verbally, have composmentis awareness and are cooperative and willing to sign informed consent. All analyses use Spearman Rank. With ethical number 068 / Kom.EtikRSWN / VI / 2025. The results show that. According to the results of the Spearman rank statistical test, it shows a significant relationship of 0.000 <0.05 and a coefficient of +0.718, which indicates a positive relationship with strong strength. The better the quality of life received by breast cancer patients, the higher their psychological well-being.